A Combined Experimental and Computational Study of Gas Sensing by Cu3SnS4 Nanoparticulate Film: High Selectivity, Stability, and Reversibility for Room Temperature H2S Sensing. Issue 10 (26th February 2018) - M, Thripuranthaka; Sharma, Neha; Das, Tilak; Varhade, Swapnil; Badadhe, Satish S.; Thotiyl, Musthafa Ottakam; Kabir, Mukul; Ogale, Satishchandra
Abstract: Several binary sulfides are used for sensing of gases such as NH3, NO2, and H2, but not for H2 S, especially at room temperature, because of the relative inactivity of metal sulfide surface bonds for this gas. The situation can be entirely different in the ternary case, however, due to the possible synergy of interactions involving dual cation surface chemistry. This is borne out by the present work wherein the Cu3 SnS4 material, the Cu‐rich ternary sulfide used for the first time in the gas sensing context, not only senses H2 S at room temperature but also remarkably does so with high selectivity and stability. Thus, a combined experimental and computer modeling study on the use of nanocrystalline orthorhombic Cu3 SnS4 phase is reported for H2 S sensing. The material shows sensitivity for a wide range of H2 S concentrations (from 10 to 2000 ppm). The performance of the sensing device fabricated on Kapton substrate remains intact even after several days and multiple bending cycles. Importantly, these experimental findings are consistent with the results of density functional theory calculations for binding energies for different gases, namely, H2 S, NO2, NH3, and CO, on Cu3 SnS4 surface. Abstract : Cu3 SnS4, a Cu‐rich ternary sulfide, is used for the first time in the gas sensing context. It not only senses H2 S at room temperature, but also remarkably does so with high selectivity and stability. The selectivity is explained by density functional theory calculations that reveal distinctive features vis‐à‐vis binary sulfides.